Phosphoproteomic Profiling of Rat’s Dorsal Root Ganglia Reveals mTOR as a Potential Target in Bone Cancer Pain and Electro-Acupuncture’s Analgesia - Wang, Wen; Zhou, You; Cai, Yangqian; Wang, Sisi; Shao, Fangbing; Du, Junying; Fang, Junfan; Liu, Jinggen; Shao, Xiaomei; Liu, Boyi; Fang, Jianqiao; Liang, Yi (Frontiers in Pharmacology, 2021)
Bone cancer pain (BCP) is a clinical refractory mixed pain involving neuropathic and inflammatory pain, with underlying mechanisms remaining largely unknown. Electro-acupuncture (EA) can partly alleviate BCP according to previous research. We aim to explore the proteins and major pathways involved in BCP and EA treatment through phosphoproteomic profiling. BCP rat model was built by tibial inoculation of MRMT-1 mammary gland carcinoma cells. Mechanical hyperalgesia determined by paw withdrawal thresholds (PWTs) and bone destruction manifested on the radiographs confirmed the success of modeling, which were attenuated by EA treatment. The differential expressed phosphorylated proteins (DEPs) co-regulated by BCP modeling and EA treatment in rat dorsal root ganglions (DRGs) were analyzed through PEX100 Protein microarray. Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis revealed that DEPs were significantly enriched in mammalian target of rapamycin (mTOR) signaling pathway. The phosphorylations of mTOR at Ser2448 and Thr2446 were increased in BCP and down-regulated by EA. In addition, the phosphorylation of S6K and Akt, markers of the mTOR complex, were also increased in BCP and down-regulated by EA. Inhibition of mTOR signaling alleviated the PWTs of BCP rats while the mTOR agonist impaired the analgesic effect of EA. Thus, our study provided a landscape of protein phosphorylation changes in DRGs of EA-treated BCP rats and revealed that mTOR signaling can be potentially targeted to alleviate BCP by EA treatment.